Mechanical properties: wood lumber versus plastic lumber and thermoplastic composites - Dias, Bernardo Zandomenico (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2017)
Plastic lumber and thermoplastic composites are sold as alternatives to wood products. However, many technical standards and scientific studies state that the two materials cannot be considered to have the same structural behaviour and strength. Moreover, there are many compositions of thermoplastic-based products and plenty of wood species. How different are their mechanical properties? This study compares the modulus of elasticity and the flexural, compressive, tensile and shear strengths of such materials, as well as the materials’ specific mechanical properties. It analyses the properties of wood from the coniferae and dicotyledon species and those of commercialized and experimental thermoplastic-based product formulations. The data were collected from books, scientific papers and manufacturers’ websites and technical data sheets, and subsequently compiled and presented in Ashby plots and bar graphs. The high values of the compressive strength and specific compressive and tensile strengths perpendicular to the grain (width direction) shown by the experimental thermoplastic composites compared to wood reveal their great potential for use in compressed elements and in functions where components are compressed or tensioned perpendicularly to the grain. However, the low specific flexural modulus and high density of thermoplastic materials limit their usage in certain civil engineering and building applications.